Service Experience Varies: Exploring the Association between Military Service and Prison Misconduct among State Inmates. Issue 4 (7th August 2020) - Brooke, Erika J.
ABSTRACT: Military service is a life event that has the ability to shape veterans' criminal trajectories. Institutional behavior has implications for community adjustment and can provide insight into offending patterns of inmates' post-release. This study explores whether military service variables affect the likelihood and frequency of prison misconduct among a nationally representative sample of U.S. state prisoners. Results suggest that variations in the military experience affect prison misconduct, especially for those who served for longer periods of time and who enter service at an older age. Recommendations for future research and suggestions for correctional policy and practice are offered.